Non-syndromic and syndromic defects in children with extracranial germ cell tumors: data of 2610 children registered with the German MAKEI 96/MAHO 98 registry compared to the general population - Schultewolter, Judit H.; Rißmann, Anke; Schweinitz, Dietrich von; Frühwald, Michael; Blattmann, Claudia; Fischer, Lars; Lange, Björn Sönke; Wessalowski, Rüdiger; Fröhlich, Birgit; Behnisch, Wolfgang; Schmid, Irene; Reinhard, Harald; et al. (Cancers, 2024)
GCTs are developmental tumors and are likely to reflect ontogenetic and teratogenetic determinants. The objective of this study was to identify syndromes with or without congenital anomalies and non-syndromic defects as potential risk factors. Patients with extracranial GCTs (eGCTs) registered in MAKEI 96/MAHO 98 between 1996 and 2017 were included. According to Teilum’s holistic concept, malignant and benign teratomas were registered. We used a case–control study design with Orphanet as a reference group for syndromic defects and the Mainz birth registry (EUROCAT) for congenital anomalies at birth. Co-occurring genetic syndromes and/or congenital anomalies were assessed accordingly. Odds ratios and 95% confidence intervals were calculated and p-values for Fisher’s exact test with Bonferroni correction if needed. A strong association was confirmed for Swyer (OR 338.6, 95% CI 43.7–2623.6) and Currarino syndrome (OR 34.2, 95% CI 13.2–88.6). We additionally found 16 isolated cases of eGCT with a wide range of syndromes. However, these were not found to be significantly associated following Bonferroni correction. Most of these cases pertained to girls. Regarding non-syndromic defects, no association with eGCTs could be identified. In our study, we confirmed a strong association for Swyer and Currarino syndromes with additional congenital anomalies.